2021
DOI: 10.3390/jimaging7080122
|View full text |Cite
|
Sign up to set email alerts
|

Non-Contact Automatic Vital Signs Monitoring of Infants in a Neonatal Intensive Care Unit Based on Neural Networks

Abstract: Infants with fragile skin are patients who would benefit from non-contact vital sign monitoring due to the avoidance of potentially harmful adhesive electrodes and cables. Non-contact vital signs monitoring has been studied in clinical settings in recent decades. However, studies on infants in the Neonatal Intensive Care Unit (NICU) are still limited. Therefore, we conducted a single-center study to remotely monitor the heart rate (HR) and respiratory rate (RR) of seven infants in NICU using a digital camera. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 69 publications
0
20
0
Order By: Relevance
“…Therefore, it is robust no matter what movement the babies make. Another advantage is that it is fast and convenient compared with training a neonatal face classifier [ 32 , 33 ].…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, it is robust no matter what movement the babies make. Another advantage is that it is fast and convenient compared with training a neonatal face classifier [ 32 , 33 ].…”
Section: Methodsmentioning
confidence: 99%
“…Similarly to adult-based existing work, the majority of past works in the neonatal space have focused on deep learning-based methods [1]- [3], [9]. In particular, the YOLO framework has been especially popular [1], [2], [9].…”
Section: B Neonatal Face and Facial Landmarks Detectionmentioning
confidence: 99%
“…However, it has been suggested that more research is needed for dark-skinned subjects and dark ambient conditions. Further, Khanam et al [21] used a CNN for the ROI selection and noise-assisted signal decomposition to supress the noise in the extracted respiratory signal.…”
Section: Related Workmentioning
confidence: 99%